P024 Treatment patterns of biologic therapies used to treat ulcerative colitis: A retrospective database analysis in the United States. (July 2019) - Erin, Comerford; Marco, DiBonaventura; Timothy, Smith; Anthony, Louder; David, Gruben; Leonardo, Salese; Daniel, Quirk
Abstract : BACKGROUNDs: Treatment goals for ulcerative colitis (UC) focus on inducing a response and maintaining long-term disease remission. The current study sought to document the real-world treatment patterns during the first year of biologic therapy in the United States. METHODS: This retrospective analysis used the PharMetrics Plus claims data from January 1, 2013 to October 1, 2017. Biologic-naïve patients aged ≥18 years with UC (ICD9:556.* or ICD10 K51.*) who newly initiated biologic therapy (adalimumab [ADA], infliximab [IFX], vedolizumab [VEDO], golimumab [GOL]) were included. Patients had to have 12 months of continuous enrollment prior to (pre-index) and after (post-index) their first biologic drug claim (index). Patients with Crohn's disease or a history of biologic therapy in the pre-index period were excluded. Treatment patterns were reported descriptively, including combination therapy (frequency of an IM with a biologic), persistence (frequency of patients using their index therapy at the end of the 12-month post-index period without a 60-day gap), and adherence (calculated based on the proportion of days covered). RESULTS: A total of N = 3, 595 patients with UC were included (51.7% male; age = 42.4 years [SD = 13.6]; disease duration = 1.3 years [SD = 1.0]) with the following treatments at index: N = 2, 055 on ADA, N = 1, 218 on IFX, N = 152 on GOL, and N = 170 on VEDO. Use of a concomitant IM therapy at index occurred as follows: ADA = 30.75%, IFX = 32.10%, GOL = 29.61%, and VEDO = 25.29%. A total of 59.2% of patients who initiated a biologic therapy remained persistent (i.e., continued on therapy) throughout the 12-month post-index observation period. This varied by therapy: ADA = 56.2%, IFX = 64.9%, GOL = 44.1%, and VEDO = 69.4%. Non-persistent patients predominantly discontinued without switching to another medication or restarting their original medication (discontinuation rates ranged from 42.3% to 52.7% among ADA, GOL, and IFX patients). However, non-persistent VEDO patients predominantly restarted the same therapy after a ≥60 day discontinuation period (36.5%). Switching therapies immediately (i.e., less than 60 days) was also common across each treatment (ADA = 27.1%, IFX = 31.2%, GOL = 31.0%, VEDO = 28.9%). Adherence to biologic therapy, measured by the proportion of days covered, were as follows: ADA = 0.72, IFX = 0.81, GOL = 0.69, VEDO = 0.84. CONCLUSION(S): For UC patients initiating biologic therapy, at least 25% initiated concomitant IM therapy. A significant number (40%) of patients discontinued their biologic therapy within the first 12 months. These findings suggest a number of patients experience suboptimal levels of disease control within the first year of biologic therapy.